2020
DOI: 10.1186/s13045-020-00954-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 binds platelet ACE2 to enhance thrombosis in COVID-19

Abstract: Background: Critically ill patients diagnosed with COVID-19 may develop a pro-thrombotic state that places them at a dramatically increased lethal risk. Although platelet activation is critical for thrombosis and is responsible for the thrombotic events and cardiovascular complications, the role of platelets in the pathogenesis of COVID-19 remains unclear. Methods: Using platelets from healthy volunteers, non-COVID-19 and COVID-19 patients, as well as wild-type and hACE2 transgenic mice, we evaluated the chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
829
5
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(957 citation statements)
references
References 87 publications
37
829
5
21
Order By: Relevance
“…Elevated soluble P-selectin levels and platelet flow cytometric studies suggest increased activation of endothelium and/or circulating platelets in COVID-19 patients [102]. Evidence of a direct stimulatory role of SARS-CoV-2 Spike protein upon platelets has also recently been presented [64]. Severe COVID-19 illness is associated with increased platelet activation as well as platelet-monocyte aggregation [104].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated soluble P-selectin levels and platelet flow cytometric studies suggest increased activation of endothelium and/or circulating platelets in COVID-19 patients [102]. Evidence of a direct stimulatory role of SARS-CoV-2 Spike protein upon platelets has also recently been presented [64]. Severe COVID-19 illness is associated with increased platelet activation as well as platelet-monocyte aggregation [104].…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of platelet aggregation in the patients was similarly observed to be greater in response to lower concentrations than higher concentrations of several platelet agonists [63]. Zhang et al [64] have very recently taken such analysis still further, reporting their detection of ACE2 expression by platelets, the direct stimulatory effects of SARS-CoV-2 or its Spike protein on platelets, and the ability of recombinant human ACE2 protein or anti-Spike monoclonal antibody to inhibit Spike protein-induced platelet activation. Hottz et al [104]have further recently demonstrated increased platelet-monocyte interaction and associated tissue factor expression by monocytes in severe COVID-19 patients.…”
Section: Plateletsmentioning
confidence: 99%
“…Viruses can also activate platelets through indirect interactions with FcγRIIA, a mechanism that may take place uniquely if antibodies directed against SARS‐CoV‐2, or cross‐reacting antibodies against more common coronaviruses that generate minor cold symptoms in humans (229E, NL63, OC43, and HKU1), are present 22 . A mechanism in which SARS‐CoV‐2 directly activates megakaryocytes and platelets appears possible as two independent studies have reported the presence of SARS‐CoV‐2 mRNA in platelets of some COVID‐19 patients 9,12 . However, how SARS‐CoV‐2 interacts with megakaryocytes and platelets has not fully been elucidated and remains controversial.…”
Section: Platelet Activation and Hyperactivty In Covid‐19mentioning
confidence: 99%
“…A postmortem evaluation of peripheral lungs from COVID-19 patients revealed diffuse alveolar damage, severe endothelial injury, and widespread thrombosis with microangiopathy [ 6 ], while an increasing number of reports discussing the role of platelet activation and aggregation in patients with severe COVID-19 is being published [ 7 , 8 ]. Molecular techniques, including transcriptomics, have been able to demonstrate platelet hyperactivity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%